Experimental Study on Freeze-Thaw Cycle Duration of Saturated Tuff. (24th July 2020) - Huang, Man; Tang, Bin; Jiang, Jianliang; Guan, Renqiu; Wang, Huajun
Abstract : The freeze-thaw duration is one of the important factors affecting the change of rock properties. However, this factor has not formed a unified standard in the freeze-thaw cycle test. This study uses saturated tuff samples taken from eastern Zhejiang, China, as research objects to explore the change law of the time required for the rock to reach a full freeze-thaw cycle. Measured results show that the total duration of the freeze-thaw cycle presents an increasing power function with the increase in the number of freeze-thaw cycles. The freezing process is divided into three phases: initial freezing, water-ice phase transition, and deep freezing. The melting process is also divided into three phases: initial melting, ice-water phase transition, and deep melting. The time required for the ice-water phase change stage of the melting process does not change with the increase in the number of freeze-thaw cycles, while the other stages increase as a power function. The proportion of duration of each stage in the freezing process does not change with the increase in the number of cycles. By contrast, the duration proportion of the initial melting phase in the melting process decreases, and the deep melting phase increases. Experimental results of the freeze-thaw cycles of tuff demonstrate that the freeze-thaw duration of the freeze-thaw cycles within 40 times can be set to 9 h. The freezing and melting processes are 6 and 3 h, respectively.